Caffeine improves swimming speed, decreases the rate of perceived exertion and lactate concentration during a high intensity intermittent aerobic training session for male swimmers - Salgueiro, D.; Balikian, P.; Andrade, V. [UNESP]; Júnior, O. (Elsevier, 2022)
Objectives: This study aimed to investigate the acute effects of caffeine on mean speed, rate of perceived effort and lactate concentration of swimmers who underwent traditional, high-intensity intermittent aerobic training sessions. Materials and methods: In this double-blind study, capsules containing either caffeine (6 mg kg−1) or placebo, were administered randomly over 2 sessions to ten male swimmers (18.2 ± 1.7 years). One hour after ingestion, the male swimmers swam ten iterations of 400 meters at heavy domain intensity, each one separated by 60 seconds of passive rest. The swimmers’ ratio perceived exertion and blood lactate levels were tested before the beginning of the test, and after the fifth and tenth iteration. Results: The swimmers’ mean speed was higher in caffeine treatment than placebo (P < 0.001). Additionally, exertion levels were lower after the fifth iteration in caffeine group compared to placebo (P < 0.001). The level of lactate was lower after the fifth and tenth iteration with caffeine ingestion compared to placebo (P < 0.001). In conclusion, the caffeine increased the speed and decreased the perceptual and lactacidemic responses during a traditional, high-intensity intermittent aerobic training session.
La caféine augmente la vitesse de natation, diminue le taux d'effort perçu et la concentration en lactate durant une session d'entraînement aérobie intermittente de haute intensité chez des nageurs de sexe masculin
Keywords: Anaerobic threshold; Ergogenic aids; Exercise intensity; Exercise physiology; Training